AN OVERVIEW SELF-EFFICACY AND SELF-ACCEPTANCE IN TUBERCULOSIS SUFFERERS - Setiyowati, Eppy; Hardiyanti, Hardiyanti; Setiawan, Ferry Agus; Susilo, Priyo (Jurnal Ilmu Kesehatan dan Kesehatan, 2021)
Background: Tuberculosis is still a major health problem in Indonesia, especially in the working area of the East Health Center in Surabaya, the long treatment of tuberculosis causes sufferers to have low self-efficacy and poor self-acceptance. Objective: This study aims to analyze the relationship between self-efficacy and the self-acceptance of patients with Tb. Method: The design research is an analytic study with a cross-sectional approach. The study population of 46 patients with active treatment for the last 3 months in the work area of the community Health Center in Surabaya by 46 patients. Results: A sample of 41 respondents taken by simple random sampling technique. The independent variable is self-efficacy, the dependent variable is self-acceptance. The instrument uses a questionnaire. Data analysis used the Chi-Square test with significance value α = 0.05. The results showed that of 41 respondents the majority (57.3%) had low self-efficacy, and the majority (57.3%) had poor self-acceptance. Chi-Square statistical test results obtained value ρ = 0.008 < a = 0.05 shows there is a relationship of self-efficacy with self-acceptance of patients with TB in the work area of the East Perak Health Center in Surabaya. Conclusions: Conclusions of the study that the lower the self-efficacy in patients with Tb the worse the self-acceptance and vice versa. Patients with TB should further improve their efficacy by always obeying health workers' advice and treatment regularly. The role of nurses in improving self-efficacy by providing education to sufferers and families, working together to care more, and motivate patients so that treatment success.